Determine The Effect of Capital, Labor, and Working Hours on Merchant Income in Surabaya Puncak Permai Modern Market in 2019 - Yustie, Renta; Retnowati, Diah Ayu (Jurnal Ilmu Ekonomi Terapan, 2020)
The purpose of this study is to determine the effect of capital, labor, and working hours on merchant income in Surabaya Puncak Permai Modern Market in 2019. The data used is the Cross Section with a sample size of 78. To analyze the authors use the method of multiple linear regression with the program eviews 6.0. partially the results of the real-level regression (α = 10%) capital significantly influence the income of traders with a positive coefficient of 0.615779 and probability 0.0000, labor has a significant effect on trader income with a positive coefficient of 2436698. and probability 0.0000, working hours does not significantly influence the income of traders with a positive coefficient of 515060.5 and a probability of 0.3232. Simultaneously the results of the study indicate that the variables of capital, labor and working hours have a significant effect on merchant income. With a F-Statistical probability value of 0.0000. This means that capital and labor have a positive influence on merchant income, while working hours have no significant effect on merchant income.